Disorder transitions and conformational diversity cooperatively modulate biological function in proteins. (18th April 2016) - Zea, Diego Javier; Monzon, Alexander Miguel; Gonzalez, Claudia; Fornasari, María Silvina; Tosatto, Silvio C. E.; Parisi, Gustavo
Abstract: Structural differences between conformers sustain protein biological function. Here, we studied in a large dataset of 745 intrinsically disordered proteins, how ordered‐disordered transitions modulate structural differences between conformers as derived from crystallographic data. We found that almost 50% of the proteins studied show no transitions and have low conformational diversity while the rest show transitions and a higher conformational diversity. In this last subset, 60% of the proteins become more ordered after ligand binding, while 40% more disordered. As protein conformational diversity is inherently connected with protein function our analysis suggests differences in structure‐function relationships related to order‐disorder transitions.